PROTEÇÃO SOCIAL ANTE O AVANÇO DO CONSERVADORISMO NO BRASIL: território, lugar e Política de Assistência Social - Alice Dianezi Gambardella (Universidade Federal do Maranhão, 2020)
This article aims to contribute to the debate about the complexity of Social Protection Policies in Brazil, especially to the reflections and experiences of the Public Policy of Social Assistance, in the context of the conservative liberal offensive. It analyzes the dilemmas surrounding the implementation of a Policy that seeks to ensure rights within a conservative movement that is historical and updated, supported by fundamentalist precepts that postulate the reduction of state intervention in social protection. From this context, it problematizes the criteria used to adopt the territorialization of the Social Assistance Policy, building a path of analysis that proposes different perspectives of territory and place as a starting point for reflection on Social Protection guaranteed through the Social Assistance Policy through the conservative neoliberal offensive.